Pharmacological and interventional treatment of benign prostatic obstruction: An evidence‐based comparative review. Issue 4 (3rd February 2021) - Malde, Sachin; Lam, Wayne; Adwin, Zainal; Hashim, Hashim
Abstract: Introduction: The recommended treatment for bothersome lower urinary tract symptoms (LUTS) secondary to benign prostatic obstruction (BPO) after the failure of behavioral therapy and fluid modification includes pharmacological, minimally invasive interventional, and surgical approaches. Each option has different risk and benefit profiles, and the urologist must be aware of the unique characteristics of each option in order to be able to accurately counsel the patients based on their individual values and preferences. We provide a comparative review of the commonest pharmacological and most widely performed interventional/surgical treatments for BPO, discussing the evidence for the treatment characteristics that are most useful for the practicing urologist. Methods: A search of the PubMed database was performed for articles reporting on the following treatments for LUTS due to BPO: α‐blockers, 5α‐reductase inhibitors, phosphpdiesterase‐5 inhibitors, prostatic urethral lift (Urolift), convective radiofrequency water vapor thermal therapy (Rezum), Temporary implantable Nitinol Device (iTIND), prostate artery embolization (PAE), transurethral resection of the prostate (TURP), photoselective vaporization of the prostate (PVP), Aquablation, and anatomical endoscopic enucleation of the prostate (AEEP). We performed a narrative review focussing on the following outcomes: efficacy, safety, durability, duration of catheterization, length of stay, re‐treatment rate, efficacy in special situations (enlarged median lobe, prostate size, urinary retention, and anticoagulant use), and sexual adverse events. Results: AEEP offers the greatest long‐term improvement in maximum flow rate, IPSS, and prostate volume reduction, with lowest re‐treatment rate, followed by PVP, TURP, and Aquablation. Urolift, Rezum, and PAE have similar efficacy for prostate volume up to 80cc, and all are more effective than the pharmacological treatment. Urolift offers the lowest rate of sexual dysfunction, followed by Rezum, and both can be performed as a day case under local anesthesia. Conclusion: Several treatment options exist to treat voiding LUTS due to BPO. Newer minimally invasive treatments reduce the hospital stay and postoperative complications, whereas AEEP provides the greatest long‐term symptom improvement at the expense of higher morbidity and sexual dysfunction. Men should be counseled regarding all suitable treatment options as some may favor reduced efficacy in association with reduced side effects.